Wood pellet heating systems the Earthscan expert handbook on planning, design and installation - Jenkins, Dilwyn (Earthscan, 2010)
Wood Pellet Heating Systems is a comprehensive handbook covering all aspects of wood pellet heating technology. The use of wood pellets as an alternative heating fuel is already well established in several countries and is becoming widespread as fossil fuel prices continue to rise and awareness of climate change grows. Wood pellets are a carbon-neutral technology, convenient to use, and can easily be integrated into existing central heating systems or used in independent space heaters. This fully-illustrated and easy-to-follow guide shows how wood-pellet heating works, the different types of s.
Keywords: Stoves, Wood -- Handbooks, manuals, etc.; Wood pellets -- Handbooks, manuals, etc.; Dwellings -- Heating and ventilation -- Handbooks, manuals, etc.; elektronické knihy; electronic books